Conventional clinical and pathological features fail to accurately predict recurrence in patients with gastric cancer staged N0. Issue 4 (April 2015) - Tavares, Amelia; Viveiros, Fernando; Maciel, Jorge; Dinis-Ribeiro, Mário
<x xml:space="preserve">Abstract</x> Introduction Despite the medical-surgical advances, even after R0 gastric resections, some patients without apparent metastatic disease develop cancer recurrence and eventually die. Aims We aimed to define recurrence in patients with node-negative gastric adenocarcinoma and to determine whether any clinicopathological features are predictive for recurrence. Materials and methods This was a retrospective cohort study on patients with gastric adenocarcinoma, consecutively diagnosed at our institution, staged as N0M0 between January 2000 and December 2008. Results We recruited 129 patients; 53% were men and 56% were older than 60 years. A total of 22% of the patients developed recurrence, with a mortality rate of 93%. Overall, 71% of the patients, N0, with recurrence presented lymphatic permeation. In univariate analysis, on comparing recurrent patients with those with no recurrence, age, size, T status, lymphatic, and venous permeation were factors that were associated significantly with recurrence, but in multivariate analysis, only age (odds ratio:19.5; 95% confidence interval: 2.3–168; P=0.008) and venous permeation (odds ratio: 6.34; 95% confidence interval: 1.8–22.8; P=0.005) were associated with recurrence. On the basis of only these two factors, the proportion of missed recurrent patients by age and venous permeation was 13 and 39%, respectively. Conclusion A total of 22% of patients, N0, developed recurrence of their disease. Age and venous permeation were independent risk factors for recurrence, but on the basis of these factors, up to 40% of patients may be missed for recurrence. New methods to predict recurrence are needed.